Analysis of the Implementation of the Independent Curriculum in Pioneer Schools to Foster Student Independence in History Subject for 10th Grade at SMAN 4 Palu - Charles Kapile; Nuraedah Nuraedah; Priyatna Prasetyawati (Dinasti International Journal of Education Management And Social Science, 2024)
The research problem is formulated as follows: "How is the implementation of the Independent Curriculum in Pioneer Schools fostering student independence in the History subject for 10th-grade students at SMAN 4 Palu?" The research aims, specifically, to analyze how the Independent Curriculum in Pioneer Schools nurtures student independence in the History subject for 10th graders at SMAN 4 Palu. This analysis is expected to lead to innovation in education, namely the creation of an ISBN-registered book: Local Content of Social Change and the Heritage of the 19th-Century Palu Kingdom as a Supplementary Independent Learning-Based Curriculum Module for the 10th Grade History Research material. The primary research output will be a nationally recognized article, indexed in Sinta 3, titled "Implementation of the Independent Curriculum in Pioneer Schools to Foster Student Independence in the History Subject for 10th-Grade Students at SMAN 4 Palu." Additionally, a teaching module and a local content book will be produced, which are practical applications to be prepared for the next research scheme. The plan is designed over a one-year period to reach Technology Readiness Level (TRL) 5, with the first year's focus on developing the teaching module. It will be implemented in sample schools and then scaled for broader use in schools and the community, particularly targeting 10th-grade high school students, ensuring it reaches TRL 5 for ready application in both schools and the wider community.